(untitled) (Ames, Iowa, 2008)
Avian Influenza provides the first comprehensive guide covering the full spectrum of this complex and increasingly high-profile disease, its history and its treatment and control. All aspects of avian influenza are dealt with in depth, systematically covering biology, virology, diagnostics, ecology, epidemiology, clinical medicine, and the control. The book fuses coverage of the latest discoveries in the basic sciences with a practical approach to dealing with the disease in a clinical setting, and providing instruction and guidance for veterinarians and government animal health officials encountering this disease in the field.
Keywords: Avian influenza,Influenza in birds,Disease outbreaks,Influenza A Virus, H1N1 subtype,Influenza, human; Prevention and control,Prevention and control,Pathogenicity,Prevention and control